MENGHIDUPKAN KEMBALI TRADISI RELIGIUS : PERSPEKTIF MASYARAKAT DESA LANDIPO TERHADAP KEGIATAN KEAGAMAAN DI MASJID AL-ABRAR DESA LANDIPO - Nurjannah, Nurjannah; Absa, Alifka Dita Olivia; Elisnawati; Husna; Prasetio, Muhammad Ardi; Faturrahman, Muhammad Bagus; Aswan; Amalia, Hilda Ayu Melvi (INSANIYAH, 2025)
Studying religious knowledge is an important thing that we must instill in the younger generation so that they can practice and continue the teachings that Allah SWT revealed to the Prophet Muhammad SAW. As we know, teaching religious knowledge is like providing a field of reward that, if the children continue to practice it, will flow with rewards even after we are gone. The background of the Landipo Village community was once a religious village, but it has gradually faded. This service article aims to determine the perception of the Landipo Village community towards religious activities carried out by students of the Kendari IAIN Real Work Lecture (KKN) in 2025, whether it has a positive impact or not. The religious activities in question include learning to recite the Qur'an, introduction and guidance on makhorijul huruf, and teaching fiqh ibadah. This community service article uses the PAR (Participatory Action Research) method, which is a method of community service that places the community as actors, not just research objects. The results of the study show that the people of Landipo Village responded positively to these activities, as they were considered to be able to increase religious understanding, improve Quran recitation, and strengthen the community's faith. In addition, the activities carried out by KKN students were considered relevant to the needs of the community and contributed to building young people with noble character. This study recommends that similar programs be implemented on an ongoing basis, involving more elements of society.